2013
DOI: 10.1111/apa.12497
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative nutrition in extremely preterm infants undergoing surgical treatment for patent ductus arteriosus is suboptimal

Abstract: Perioperative nutrition in extremely preterm infants undergoing PDA surgery in Sweden is suboptimal and needs to be improved. The significance of malnutrition for outcome after PDA surgery remains unclear and requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…A recent systematic review found that early parenteral nutrition in preterm infants improves short‐term growth outcomes . Among very preterm infants nutrition is often suboptimal , and while there is yet no evidence linking progressive advancement of enteral milk feeds to risk of adverse short‐term outcomes, such as necrotising enterocolitis and late‐onset infection, the need for further trials is recognised .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that early parenteral nutrition in preterm infants improves short‐term growth outcomes . Among very preterm infants nutrition is often suboptimal , and while there is yet no evidence linking progressive advancement of enteral milk feeds to risk of adverse short‐term outcomes, such as necrotising enterocolitis and late‐onset infection, the need for further trials is recognised .…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, many preterm infants suffer from severe undernutrition during the first weeks of life 152 . This insufficient nutritional status is not just present in infants with fluid restriction 153 . The current recommendations for preterm infants are to provide nutrients that are approximately the same as the requirements for the rate of growth and composition of weight gain for a normal fetus of the same conceptional age.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal and morbidity data within the EXPRESS cohort were prospectively registered in the Swedish neonatal quality register by physicians and nurses and has previously been published [1,18], nutritional intakes regarding infants who underwent PDA-surgery has also been published [17]. Briefly, detailed nutritional intakes were retrospectively obtained from hospital records for the perioperative week from three days pre-surgery (-3 days), day of surgery (day 0) to three days post-surgery (þ3 days).…”
Section: Data Collectionmentioning
confidence: 99%
“…Energy and macronutrient intakes from enteral nutrition and parenteral nutrition were calculated using information from the manufacturers and breast milk analyses [6]. Nutritional intakes of energy, macronutrients and fluids were assessed in kcal/kg/day, grams/kg/day and mL/kg/day, respectively [6,17]. Nutritional intakes during the perioperative week were compared between NICUs and to minimal estimated nutritional needs of 110 kcal/kg/day, 4 g protein/kg/day, 4.8 g fat/kg/day, and 12 g carbohydrates/100 kcal [17], based on international nutritional guidelines [7,21].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation